Resources and the political economy of state fragility in conflict states: Iraq and Somalia - Ghassan Dibeh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper studies state failure and governance in two conflict-states in the Middle East: Iraq and Somalia. Iraq is currently undergoing a social experiment under which a new form of government is being constructed after the passage of autocratic rule. The government envisaged is a consociational democratic state designed a priori as a political mechanism for the redistribution of resources, mainly oil. Somalia represents a stateless society or anarchy. The paper argues that in resource-rich countries such as Iraq, the consociational project leads to an Olson-type rent-seeking confessional behaviour that hampers economic growth and development. The rent-seeking behaviour in Iraq is fuelling the insurgency that perceives the consociational system as a grabbing.
Keywords: D72; D74; N45; N55; 330; fragile states; political economy; resources; Politischer Konflikt; Staatsversagen; Entwicklung; Rohstoffressourcen; Rent Seeking; Irak; Somalia